2020
DOI: 10.1051/0004-6361/202038860
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the total molecular gas in galaxies: [CII] and the CO-dark gas

Abstract: Context. Molecular gas is a necessary fuel for star formation. The CO (1−0) transition is often used to deduce the total molecular hydrogen but is challenging to detect in low-metallicity galaxies in spite of the star formation taking place. In contrast, the [C ii]λ158 µm is relatively bright, highlighting a potentially important reservoir of H 2 that is not traced by CO (1−0) but is residing in the C +-emitting regions. Aims. Here we aim to explore a method to quantify the total H 2 mass (M H 2) in galaxies a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
136
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 171 publications
(226 reference statements)
20
136
2
Order By: Relevance
“…This idea is supported by the observation that this region has the lowest best-fitting SED metallicity of all the regions observed (see Table 2), a condition that may be conducive to CO-dark molecular gas (Wolfire et al 2010). Recent studies of lowmetallicity regions in galaxies (Madden et al 2020) show that most of the CO is dissociated in these environments, making [C II] a better tracer of molecular gas in these particular regions. Region I, which lies close to the end of the continuum radio jet in the south, will be discussed in the next subsection in the context of possible ISM heating by the jet.…”
Section: Infrared Diagnosticsmentioning
confidence: 66%
See 2 more Smart Citations
“…This idea is supported by the observation that this region has the lowest best-fitting SED metallicity of all the regions observed (see Table 2), a condition that may be conducive to CO-dark molecular gas (Wolfire et al 2010). Recent studies of lowmetallicity regions in galaxies (Madden et al 2020) show that most of the CO is dissociated in these environments, making [C II] a better tracer of molecular gas in these particular regions. Region I, which lies close to the end of the continuum radio jet in the south, will be discussed in the next subsection in the context of possible ISM heating by the jet.…”
Section: Infrared Diagnosticsmentioning
confidence: 66%
“…The region shaded in yellow cannot be explained in terms of pure PDR emission, but requires either an excess of [C II] emission or a deficit of CO emission. Most of the normal and star-forming local galaxies lie in the blue region, while higher ratios are measured for dwarf galaxies and lower metallicity galaxies (Madden et al 2020).…”
Section: Relative Strength Of Co and [C Ii] Emissionsmentioning
confidence: 92%
See 1 more Smart Citation
“…We note that [C ii] is considered to be a good tracer of CO-dark molecular gas (e.g. Cormier et al 2015;Accurso et al 2017b;Zanella et al 2018;Madden et al 2020). Even though [C ii] can originate from both ionised gas and neutral gas, simulations and models have found that the ionised fraction does not go beyond 50%, even for metal-poor galaxies (Accurso et al 2017a;Cormier et al 2019).…”
Section: Ir and Sfr Versus L Comentioning
confidence: 90%
“…As carbon has an ionisation potential of 11.2 eV, below that of hydrogen, [C ii] is detected in regions of both predominantly neutral and ionised gas. The line luminosity has been found to correlate with the star formation rate (SFR) in normal, star-forming galaxies (Stacey et al 2010;De Looze et al 2011Herrera-Camus et al 2015;Schaerer et al 2020) and has also been proposed as a gas mass tracer (e.g., Zanella et al 2018;Madden et al 2020). As the emission wavelength is redshifted into the submillimetre and millimetre bands, the [C ii] is recognised as an important probe of the ISM of high-z galaxies.…”
Section: Introductionmentioning
confidence: 99%